If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(X + -2) = 72 Reorder the terms: 8(-2 + X) = 72 (-2 * 8 + X * 8) = 72 (-16 + 8X) = 72 Solving -16 + 8X = 72 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 8X = 72 + 16 Combine like terms: -16 + 16 = 0 0 + 8X = 72 + 16 8X = 72 + 16 Combine like terms: 72 + 16 = 88 8X = 88 Divide each side by '8'. X = 11 Simplifying X = 11
| 0=-3x-2y-5 | | 18*18=6x*24x | | 8=92-8x | | 8-e=e | | 6+15y=39 | | (x-1)(x+2)=2(x-4)(x+4) | | 3x+9=3x-8 | | 13+g=31 | | 2p-3r=7 | | 5c=24-c | | t+15=27 | | 64-8x=4x+4 | | 3a+10+5a=-35 | | 4(8-5y)=-2y-4 | | 9x+4=-7 | | 7x+70=14 | | 6x-27=1.8 | | 4=2*3 | | 282.286=2*30.1754+L | | Y=3.5+46 | | 10=(x-2)+2 | | 19u+v-6u+4v= | | f(2)=7*2-5 | | 2(3n-4)=34 | | 2.3=4 | | 0.20+0.60(400)=0.30(400+x) | | 4n+1=37 | | b^2=-15b-56 | | 7=m+2 | | 3+1.75=9.25 | | 60-9x=48 | | 2x+29x=180 |